Corporate Income Tax Harmonization and Capital Allocation : Corporate Income Tax Harmonization and Capital Allocation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
The IMF Working Papers series is designed to make IMF staff research available to a wide audience. Almost 300 Working Papers are released each year, covering a wide range of theoretical and analytical topics, including balance of payments, monetary and fiscal issues, global liquidity, and national and international economic developments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Business Taxes and Subsidies; Taxation, Subsidies, and Revenue